1972
DOI: 10.1121/1.1913082
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Sound in Ducts with Thin Shear Layers—Convergence to the Uniform Flow Case

Abstract: The problem of the transmission of sound in a duct with very thin shear layers at the walls is treated by an inner expansion method. The results show that the formulation of the problem of the transmission of sound in a duct with a shear layer at the wall converges, in the case of a vanishingly thin shear layer, to the formulation of the same problem when uniform flow is assumed and the wall boundary condition is that of continuity of particle displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 0 publications
2
84
0
Order By: Relevance
“…The reason for this decision appears to be based on the work of Eversman and Beckemeyer 7 in which it was demonstrated that in the limiting case as the boundary layer thickness tends to zero, the boundary condition reduces to that of continuity of particle displacement. Thus, for at least a brief period in history, the question of the proper wall impedance boundary condition to be used for a mean flow model with slip seems to have been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this decision appears to be based on the work of Eversman and Beckemeyer 7 in which it was demonstrated that in the limiting case as the boundary layer thickness tends to zero, the boundary condition reduces to that of continuity of particle displacement. Thus, for at least a brief period in history, the question of the proper wall impedance boundary condition to be used for a mean flow model with slip seems to have been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (11) boundary condition, with ∂v ′ /∂t on the right hand side of (11) given by either boundary condition (5) or (9). This may be contrasted against the direct method written in the same form,…”
Section: Using Characteristics To Apply the Boundary Conditionmentioning
confidence: 99%
“…For flat surfaces where (n ·∇u 0 )·n ≡ 0, equation (1) was shown by Eversman and Beckemeyer [9] and Tester [10] to be the correct limit of an infinitely thin inviscid boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…This condition assumes an infinitely thin boundary layer, and effectively uses a vortex sheet model where the continuity of pressure and normal displacement is applied [16,39,15]. In the limit of an infinitely small source (w → 0) the present test case is equivalent to the benchmark problem proposed in reference [8] and for which a complete analytical solution has been made available.…”
Section: Problem Descriptionmentioning
confidence: 99%